PROXIMITY COMMUNICATION METHOD AND APPARATUS - LIM, Chae-Man; LEE, Hyoung-Joo; KIM, Tae-Yoo (2024)
A method of controlling a communication module by an electronic device is provided. The method includes receiving, by a second processor, a specified signal from a first processor informing that the first processor enters an inactive state from an active state, by a second processor, and controlling, by the second processor, a Wireless Fidelity (WiFi) communication function in response to the specified signal. According to an operation state of the first processor, that is, an inactive state such as a sleep state or a power off state, or an active state, a subject which processes WiFi communication is changed. Accordingly, it is possible to efficiently and continuously monitor WiFi communication data and process the WiFi communication data on an accurate period.